1994
DOI: 10.1148/radiology.192.2.8029423
|View full text |Cite
|
Sign up to set email alerts
|

Balloon dacryocystoplasty: results in the treatment of complete and partial obstructions of the nasolacrimal system.

Abstract: Balloon DCP is simple and safe but has high failure and recurrence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 0 publications
2
35
0
3
Order By: Relevance
“…8,10,15 In this study, the longterm success rate of BD for junctional obstructions was similar and calculated as 50%. The reason for this low success rate may be the irregular morphology of the lacrimal sac lumen, where the soft-tipped guidewire could not be negotiated through adhesions between lacrimal sac walls.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…8,10,15 In this study, the longterm success rate of BD for junctional obstructions was similar and calculated as 50%. The reason for this low success rate may be the irregular morphology of the lacrimal sac lumen, where the soft-tipped guidewire could not be negotiated through adhesions between lacrimal sac walls.…”
Section: Discussionsupporting
confidence: 61%
“…However, there are less favourable long-term patency rates for the management of idiopathic canalicular and subcanalicular LDS obstructions, reported between 20 and 35.5%. 8,10 In our previous study, the overall patency rate of BD was calculated as 66.2% for canalicular and subcanalicular lesions in the mean follow-up period of 13 months. In this study, the overall patency rate was 54.5% after a mean follow-up period of 100 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be performed through an antegrade or through a retrograde technique. 6 -9 The reported munk at follow-up success of dacryocystoplasty alone ranges widely, from 25% to 50% 6,8 to 90%. 9,11 When (antegrade) dacryocystoplasty was combined with silicone intubation, two studies showed a six-month success rate of 56% to 60% in patients with incomplete NLD obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…3 .4 Reported success rates for balloon DCP are widely variable, ranging from 23% to 90%. 5,6 The aim of this study was to determine the efficacy of DCP with balloon dilation in the treatment of acquired obstruction of the nasolacrimal system in adults in our unit.…”
mentioning
confidence: 99%